Synthesis of Some Substituted Furans and Endoperoxides Via Singlet Oxygen Reactions - YASSIR AL-JAWAHERI; Noor M. Mahdi (College of Education for Pure Sciences, 2021)
Cinnamaldehyde was used to condense with substituted acetophenone then with acetone to form substituted 2,4- diene -1- pentanone (1- 4), after two moles of cinnamaldehyde condense with one mole of acetone to form 1, 5- diphenyl nona- 8- tetraene -5 - one (5), for these reactions, sodium hydroxide was used as a catalyst, the resulted compounds reduced by Luche (specific reduction agent use cerium chloride as a catalyst with sodium borohydride to protect double bond) reaction to form 2,4- diene-1- methoxy pentane (6-9) and -5- methoxy nona- 1,3,6,8 - tetraene - 1,9 - diyl dibenzene (10), the resulted dienes compound converted to endoperoxides (11- 15) via singlet oxygen reaction in the present of Rose Bengal as a catalyst with light in chlorinated solvent and finally by appling of Appel reaction condition these compounds converted to furans (16- 20). All mechanisms of the reaction were listed. These compounds were identified by thin layer chromatography TLC, and by their physical properties in addition, the IR spectroscopy and 1HNMR.